Formazione Green al Nautico S. Giorgio per cittadini attivi e consapevoli - Casarino, Alessandra; Caliman, Tiziana (Chimica nella Scuola, 2024)
The study presents an innovative, multidisciplinary laboratory for education and training in ecological transition, involving students directly in monitoring nitrogen dioxide levels around their residences. This study aims to understand the primary causes of air pollution to enhance attention to eco-sustainability and climate change as a significant segment of the educational curriculum in Italian schools. Italian schools have a long-standing tradition of developing projects aimed at fostering an understanding of the intricate relationship between humans and the environment. These educational initiatives promote the integration of various school disciplines and environmental education, assisting students in synthesizing knowledge and viewing their academic learning as a tool to comprehend both local and global realities. Furthermore, they help students recognize their roles as active citizens who can contribute to intergenerational air quality preservation through informed and rational choices.